VOICE DIRECTION IN UZBEK DUBBING ART DEVELOPMENT PROCESSES (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
This article demonstrates the history of the development of Uzbek dubbing. The rich historical experience of important figures in the beginning of the new century and modern Uzbek dubbing art will be analyzed in detail. Emphasis will be placed on the work done and planned in the future by our government in this area. In the end, conclusions and suggestions on the topic are given.